Xanthine oxidase activity regulates human embryonic brain cells growth - Danielyan, K.E.; Kevorkian, G.A. (Вiopolymers and Cell, 2011)
Aim. Involvement of Xanthine Oxidase (XO; EC1.1.3.22) in cellular proliferation and differentiation has been suggested by the numerous investigations. We have proposed that XO might have undoubtedly important role during the development, maturation as well as the death of human embryos brain cells. Methods. Human abortion material was utilized for the cultivation of brain cells (E90). XO activity was measured by the formation of uric acid in tissue. Cell death was detected by the utility of Trypan Blue dye. Results. Allopurinol suppressed the XO activity in the brain tissue (0.12 ± 0.02; 0.20 ± 0.03 resp., p ≤ 0.05). On day 12th the number of cells in the culture treated with the Allopurinol at the early stage of development was higher in comparison with the Control (2350.1 ± 199.0 vs 2123 ± 96) and higher in comparison with the late period of treatment (1479.6 ± 103.8, p < < 0.05). In all groups, the number of the dead cells was less than in Control, indicating the protective nature of Allopurinol as an inhibitor of XO. Conclusions. Allopurinol initiates cells proliferation in case of the early treatment of the human brain derived cell culture whereas at the late stages it has an opposite effect. Keywords: xanthine oxidase, human embryonic brain cells, proliferation, cell death.